Incorporating telemedicine into the integrated care of the COPD patient a summary of an interdisciplinary workshop held in Stresa, Italy, 7–8 September 2017. (October 2018) - Donner, Claudio F.; Raskin, Jonathan; ZuWallack, Richard; Nici, Linda; Ambrosino, Nicolino; Balbi, Bruno; Blackstock, Felicity; Casaburi, Richard; Dreher, Michael; Effing, Tanja; Goldstein, Roger; Krishnan, Jerry; et al.
Abstract: This report is a summary of a workshop focusing on using telemedicine to facilitate the integrated care of chronic obstructive pulmonary disease (COPD). Twenty-five invited participants from 8 countries met for one and one-half days in Stresa, Italy on 7–8 September 2017, to discuss this topic. Participants included physiotherapists, nurses, a nurse practitioner, and physicians. While evidence-based data are always at the center of sound inference and recommendations, at this point in time the science behind telemedicine in COPD remains under-developed; therefore, this document reflects expert opinion and consensus. While telemedicine has great potential to expand and improve the care of our COPD patients, its application is still in its infancy. While studies have demonstrated its effectiveness in some patient-centered outcomes, the results are by no means consistently positive. Whereas this tool may potentially reduce health care costs by moving some medical interventions from centralized locations in to patient's home, its cost-effectiveness has had mixed results and telemonitoring has yet to prove its worth in the COPD population. These discordant results should not be unexpected in view of patient complexity and the heterogeneity of telemedicine. This is reflected in the very limited support offered by the National Health Services to a wider application of telemedicine in the integrated care of COPD patients. However, this situation should challenge us to develop the necessary science to clarify the role of telemedicine in the medical management of our patients, providing a better and definitive scientific basis to this approach.